Eleanor's story an American girl in Hitler's Germany - Garner, Eleanor Ramrath (Atlanta, GA Peachtree, 1999)
During the Great Depression, Eleanor's family moves from America to Germany, but the war breaks out as her family is crossing the Atlantic, and for years Eleanor struggles to keep her American identity despite the turbulence and upheaval around her.
940L
85221
Keywords: Garner, Eleanor Ramrath; World War -- Germany -- 1939-1945; World War -- Personal narratives, American -- 1939-1945; World War -- Children -- Germany -- 1939-1945; World War -- Children -- United States -- 1939-1945